Treasury of children's literature - Eisen, Armand (Boston : Houghton Mifflin, 1992)
A collection of traditional and original stories and poems by such authors as Aesop and Lewis Carroll, including excerpts from "The Wind in the Willows" and "Peter Pan."
Goldilocks and the three bears -- Sleeping Beauty -- Three billy goats gruff -- Jack and the beanstalk -- Three little pigs -- Little Red Riding hood -- Aesop's fables -- Cinderella -- Hansel and Gretel -- Rapunzel -- Frog prince -- Brementown musicians -- Snow White -- Rumpelstiltskin -- Mother Goose's nursery rhymes -- Mad tea-party -- Cat and the fox again -- Piper at the gates of dawn -- Toyland and the capital of Toyland -- Hook or me this time -- Child's garden of verses -- Brer Rabbit -- Johnny Appleseed -- John Henry -- Paul Bunyan -- Night before Christmas -- Ugly duckling -- Nightingale --Steadfast tin soldier -- Emperor's new clothes -- Princess and the pea -- Little match girl -- Thumbelina.
"Ariel books."
Traditional stories, Grimm's fairy tales, Aesop's fables, American tales and fairy tales by Hans Christian Andersen retold by Sheila Black.
109006
Keywords: Children's literature; Literature - juvenile. -- Collections; Fairy tales; Juvenile works; Children's literature